Susceptibilities of Candidatus Liberibacter asiaticus‐infected and noninfected Diaphorina citri to entomopathogenic fungi and their detoxification enzyme activities under different temperatures. Issue 6 (25th March 2018) - Hussain, Mubasher; Akutse, Komivi Senyo; Lin, Yongwen; Chen, Shiman; Huang, Wei; Zhang, Jinguan; Idrees, Atif; Qiu, Dongliang; Wang, Liande
Abstract: Some entomopathogenic fungi species, Isaria fumosorosea, and Hirsutella citriformis were found to be efficient against the Asian citrus psyllid, Diaphorina citri Kuwayama (Hemiptera: Liviidae). However, the susceptibility to these fungi increases when the psyllid infected with Candidatus Liberibacter asiaticus (Las), which is transmitted by D. citri and causes citrus greening disease. In this study, we examined the Las‐infected and Las‐uninfected D . citri susceptibility to entomopathogenic fungi at different temperature regimes (5–40°C). When D. citri adults exposed to cold temperature (5°C), they showed less susceptibility to entomopathogenic fungi as compared with control (27°C). Irrespective of infection with Las, a significantly positive correlation was observed between temperature and percentage mortality caused by different isolates of I. fumosorosea, 3A Ifr, 5F Ifr, PS Ifr, and H. citriformis isolates, HC3D and 2H. In contrast, a significantly negative correlation was found between temperature and percentage mortality for 3A Ifr for both Las‐infected and Las‐uninfected psyllids. Detoxification enzymes, Glutathione S‐transferase levels in D . citri showed a negative correlation, whereas cytochrome P450 and general esterase levels were not correlated with changes in temperature. These findings revealed that detoxification enzymes and general esterase levels are not correlated with altered susceptibility to entomopathogenic fungi at the different temperature regimes. Conclusively, temperature fluctuations tested appear to be a significant factor impacting the management strategies of D. citri using entomopathogenic fungi. Abstract : Alterations in entomopathogenic fungi susceptibility to psyllids are correlated with HLB infection. Diaphorina citri were less susceptible to entomopathogenic fungi when exposed to cold temperature. Temperature affected the levels of glutathione S‐transferase, but not of cytochrome P450 and general esterase activity in psyllids.